2019
DOI: 10.1371/journal.pone.0213381
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the brain in myotonic dystrophies: A 5-year longitudinal follow-up study

Abstract: Objectives The aim of this study was to examine the natural history of brain involvement in adult-onset myotonic dystrophies type 1 and 2 (DM1, DM2). Methods We conducted a longitudinal observational study to examine functional and structural cerebral changes in myotonic dystrophies. We enrolled 16 adult-onset DM1 patients, 16 DM2 patients, and 17 controls. At baseline and after 5.5 ± 0.4 years participants underwent neurological, neuropsychological, and 3T-brain MRI ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 50 publications
2
40
1
Order By: Relevance
“…However, these results contrast with other attempts at longitudinal MRI assessment that found no loss over a period of 5 years. 7 The longer timespan employed in the present work compared with the latter, could explain the potential progression of atrophy found in this study.…”
Section: Discussionmentioning
confidence: 56%
“…However, these results contrast with other attempts at longitudinal MRI assessment that found no loss over a period of 5 years. 7 The longer timespan employed in the present work compared with the latter, could explain the potential progression of atrophy found in this study.…”
Section: Discussionmentioning
confidence: 56%
“…Future studies would also benefit from a longitudinal design. Of note, recent data from Gliem and colleagues [65] suggest the rate of structural brain change over time may be slow, and hence could be challenging to measure within the timescale of a typical clinical trial. Further, respiratory function was not specifically assessed as part of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A 5 years follow-up MRI study in DM1 and DM2 revealed mainly stable findings, but there was a mild progression of GM reduction in DM1 (17).…”
Section: Introductionmentioning
confidence: 94%
“…Effects of altered cerebral levels of myelin, calcium could theoretically play a role in susceptibility or R2 * of brain tissue. In DM1 and DM2 myelin changes due to slowly evolving demyelinating processes mainly related to formation of white matter lesions have been observed (13,17). Furthermore, dysregulation of calcium metabolism (30,31), e.g., due to calcium channel dysfunction, as discussed in the pathogenesis of restless legs symptoms (RLS) in DM2 (32) could potentially influence QSM and R2 * measures.…”
Section: Introductionmentioning
confidence: 99%